PENINGKATAN KAPASITAS ISTRI NELAYAN DALAM PENGOLAHAN HASIL PERIKANAN DI NEGERI KAILOLO - Tianotak, Ratih; Maluku, YPPM; Abrahamsz, James (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Wife has an important role in helping the family economy. Kailolo village, Subdistrict Haruku island, Central Maluku Regency is one of Village that has a fishing community. During the fishing season many fish are catches, but some fish are unsold. Fishermen’s wife has an opportunity through fish processing. However, there are several problems related to this opportunity, including: institutional problem, weak capacity on fish processing and the difficulty of raw materials during the high wave season. The purpose of this activity is to increase empowerment and the capacity of fishermen's wives in fish processing. The Participatory Rural Appraisal (PRA) approach was used in this activity. Through this approach, the community has a large role to implementing the proses. On the other hand, the results achieved were the formation of a group together with its organizational structure, increased entrepreneurship and understanding regarding licensing, processed fish products were produced and the realization of more attractive packaging labeling.